1989
DOI: 10.1111/j.1439-0434.1989.tb01086.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Infection Structures of Sderotium cepivorum on Onion

Abstract: Growth of Sderotium cepivorum mycelium on root tissue differed from that on stem tissue. Hyphae grew along the lines of the longitudinal epidermal cell walls often producing side branches which resulted in a distinctive pattern of growth. Penetration occurred mainly between anticlinal wall junctions with occasional direct penetration through the periclinal wall. Growth on the surface of the stem resulted in the formatíon of donne shaped infection cushions, arising from repeated dichotomous branching of hyphal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…(1989a ) noted infection cushion formation on leaves and the stem base; in this study infection cushions were also noted on roots. Stewart et al . (1989b ) suggested that infection cushion formation on leaf and stem, but not root tissue, was in response to the greater resistance of these tissues to penetration because of the cuticle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1989a ) noted infection cushion formation on leaves and the stem base; in this study infection cushions were also noted on roots. Stewart et al . (1989b ) suggested that infection cushion formation on leaf and stem, but not root tissue, was in response to the greater resistance of these tissues to penetration because of the cuticle.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerotium cepivorum sclerotia can survive in soil for more than 20 years ( Coley‐Smith et al ., 1990 ) and produce mycelium in response to the presence of Allium root exudates ( Coley‐Smith & Holt, 1966). The process of fungal penetration has been described ( Abd El‐Razik et al ., 1973 ; Stewart et al ., 1989a , b). Following penetration of the root epidermis, S. cepivorum invades cortical parenchyma both intra‐ and intercellularly, causing extensive tissue degradation ( Abd‐El‐Razik et al ., 1973 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extracts are the most frequently cited chemical factor inducing infection cushion formation in R. solani (Flentje et al, 1963;Marshall and Rush, 1980;Stockweiland Hanchey, 1983) as weil as in Sclerotium cepiyorum (Steward et al, 1989). Likewise, leaf diffusates were deinonstrated to not only stimulate lateral germination of Botrytis conidia, but also to enhance appressorium formation (C1ark and Lorbeer, 1976a,b).…”
Section: Chemical Signalsmentioning
confidence: 95%
“…De Bary on bean petals (Abawi et al 1975), and Sclerotium cepivorum Berk, on the stems of onion seedlings (Stewart et al 1989). It has been suggested that the type and complexity of the infection structure developed by this group of organisms is related to the degree of development of the original epiphytic hyphae (Garcia-Arenal & Sagasta 1980), the nutrient level available to the surface hyphae (Akutsu et al 1980), or the hardness of the relative strength of the tissue under attack (Stewart et al 1989). In the instance of infection on lemon, infection cushions were only formed by hyphae developing from a substantial food base such as floral remnants or an agar block.…”
Section: Discussionmentioning
confidence: 98%